2015
DOI: 10.1007/s40865-015-0014-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Patterns of Offending by Juvenile Offenders in Australia: What Is the Evidence for a Specialist Violent Offender?

Abstract: The question of whether there are offenders who specialise in violent offences is one that has been of considerable interest to life course developmental criminology as well as policy makers and the public. The current study investigated this using an administrative dataset of juvenile offenders from New South Wales, Australia. Specifically, it asked whether offenders convicted of a serious violent offence differed in their demographic, criminal history and reoffending profiles and whether there were further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…To assess this relationship, we study the relationship between violence at baseline and rearrests 7 years later and compare whether early violence and risk factors for violent offending distinguish between various offending trajectories. Based upon recent research (DeLisi et al, 2015;Harris, 2013;Mazerolle et al, 2010;McGrath, 2015), we expect early violent offending in adolescence will not be associated with more chronic patterns of offending in adulthood. However, we do expect that such offenders will engage in more diverse forms of offending in early adulthood.…”
Section: Current Studymentioning
confidence: 97%
See 4 more Smart Citations
“…To assess this relationship, we study the relationship between violence at baseline and rearrests 7 years later and compare whether early violence and risk factors for violent offending distinguish between various offending trajectories. Based upon recent research (DeLisi et al, 2015;Harris, 2013;Mazerolle et al, 2010;McGrath, 2015), we expect early violent offending in adolescence will not be associated with more chronic patterns of offending in adulthood. However, we do expect that such offenders will engage in more diverse forms of offending in early adulthood.…”
Section: Current Studymentioning
confidence: 97%
“…Some studies have shown that violent offending in adolescence might be an indicator of either heterogeneous patterns of offending (Elliott et al, 1986;Farrington, 1989;Fontaine et al, 2014) or chronic offending (Elliott, 1994;Laubacher et al, 2014;Nash & Kim, 2005;Svensson, 2002), throughout the life course. In contrast, more recent research has shown that early violence may be a poor predictor of particular criminal career patterns and/or dimensions (DeLisi et al, 2015;Harris, 2013;Mazerolle et al, 2010;McGrath, 2015).…”
Section: Violent Behavior In Mid-adolescence and Patterns Of Offending In Early Adulthoodmentioning
confidence: 97%
See 3 more Smart Citations